2020
DOI: 10.1007/s11104-020-04675-1
|View full text |Cite
|
Sign up to set email alerts
|

Differential responses of litter decomposition to warming, elevated CO2, and changed precipitation regime

Abstract: Background and aims Litter decomposition is a fundamental process of biogeochemical cycles and particularly sensitive to global change. However, the overall effects of warming, elevated carbon dioxide and changed precipitation regime on litter decomposition are not well studied. Methods To assess the effects of these three common global change factors on litter decomposition, we performed a meta-analysis using 366 pairwise observations from 103 published articles. We quantified the responses of litter decompos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 66 publications
1
26
2
Order By: Relevance
“…Increased and decreased precipitation had positive and negative effects on soil C pools, respectively (Figure 2a,b). Increase in precipitation relieves water stress (Figure S2a,b), changes microbial communities (Zhou et al, 2018), and increases enzyme activities (Ren et al, 2017), thereby promoting litter decomposition (Wu et al, 2020). More labile C is transferred to the soil through faster decomposition (Sylvia et al, 2005; Zhou, Zhou, Nie, et al, 2016), which may explain the increase in MBC, DOC, and TC observed in this study (Berg & Steinberger, 2008; Kalbitz et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Increased and decreased precipitation had positive and negative effects on soil C pools, respectively (Figure 2a,b). Increase in precipitation relieves water stress (Figure S2a,b), changes microbial communities (Zhou et al, 2018), and increases enzyme activities (Ren et al, 2017), thereby promoting litter decomposition (Wu et al, 2020). More labile C is transferred to the soil through faster decomposition (Sylvia et al, 2005; Zhou, Zhou, Nie, et al, 2016), which may explain the increase in MBC, DOC, and TC observed in this study (Berg & Steinberger, 2008; Kalbitz et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…To explore factors that regulate the effects of altered precipitation regimes on soil N cycling, the data corresponding to each observation were subdivided into six moderator groups: the precipitation type (rainfall or snowfall), ecosystem type (cropland, desert, forest, grassland, shrubland, tundra, or wetland), climate region (arid or humid regions), experimental duration (short term, <12 months; medium‐term, 12–24 months; or long term, >24 months), and magnitude of precipitation change (small, <25% change in MAP; moderate, 25%–75%; or large, >75%; Wang et al, 2021; Wu et al, 2020). The identities, levels and descriptions of the moderator variables used in this meta‐analysis are listed in Table S2.…”
Section: Methodsmentioning
confidence: 99%
“…The positive effects of N addition plus increased rainfall can be attributed to the individual positive effects of increased rainfall and neutral effects of N addition, although the magnitude was larger than the individual effects of rainfall. This could be due to the fact that increased rainfall can decrease the negative effects of N addition by diluting its excesses and hence reducing soil acidification, base cation depletion and the mobilisation of Al 3+ (Wu et al, 2020). Likewise, the more severe combined as opposed to individual effects of warming and increased rainfall could be explained by the way that additional water input mitigates the drier conditions associated with experimental warming (Yue et al, 2017).…”
Section: Combined Effects Of Multiple Gcfsmentioning
confidence: 99%
“…Their effects, however, varied between the different metrics that describe soil fauna communities. Ecosystem type is clearly an important modulator variable regulating the effects of GCFs on ecosystem functions (Wu et al, 2020;Yue et al, 2017). Yet, our study showed that ecosystem type only had a minor impact on the individual and combined effects of GCFs on soil fauna communities, thereby indicating a consistent trend in soil fauna responses to GCFs across different types of terrestrial ecosystems.…”
Section: Influences Of Modulator Variablesmentioning
confidence: 99%